(1456) PERT \ CPM techniques in planning and monitoring some agriculture projects تقنيات PERT / CPM في تخطيط ومراقبة بعض المشاريع الزراعية - El-daoushy, Abdalla (The Institute of National Planning, 2018)
This paper aims at providing the reader with the applications of Network Analysis Techniques to planning in general and to the Agricultural sector in particular. n it also aims to treat the lack of essential details ( which are very useful details to trainees in agricultural planning ) and not explored in the reference listed below.